Citsukha's contribution to Advaita : with special reference to the Tattva-pradīpikā - Sarma, V. Anjaneya (Kavyalaya Publishers, 1974)
Study on the contribution of Citsukha, 13th century Indian philosopher, to the non-dualistic (advaita) school of Hindu philosophy.